2013
DOI: 10.17221/704/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitinase-transgenic (McChit1) tobacco on the rhizospheric microflora and enzyme activities of the purple soil

Abstract: In order to evaluate the bio-security of genetically modified (GM) plants in the purple soil, we carried out a pot experiment about rhizospheric microflora at different development stages of a chitinase-transgenic (McChit1) tobacco (T-Chit), a plasmid-transgenic tobacco (T-Vi), and a non-transgenic tobacco (Nt-X) that were grown in the same purple soil, and surveyed the growth of three tobaccos and the properties of soil (i.e. the dynamic changes of the cultivable rhizospheric bacteria and fungi, soil enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…These results are in accordance with those of Wang, Shen (16), who reported that 1-year-old chitinase-transgenic (McChit1) tobacco (T-Chit) were non-toxic to the number of cultivable bacteria and fungi population in studied purple soil during tobacco growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with those of Wang, Shen (16), who reported that 1-year-old chitinase-transgenic (McChit1) tobacco (T-Chit) were non-toxic to the number of cultivable bacteria and fungi population in studied purple soil during tobacco growth.…”
Section: Discussionsupporting
confidence: 92%
“…Our knowledge of soil microbial diversity is limited in part because many groups of microbes are not cultivable in the laboratory conditions (14). Approximately 1% of the soil bacterial population can be cultured by standard laboratory practices (15, 16). The most knowledge on natural microbial community composition has been derived from indirect microbiological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, transgenic plant products in the soil may alter ecological, physical and chemical environments like soil microbial population structure and quantity. Plant and soil associated microbial diversity are affected by not only plant species and newly introduced gene but also by environmental factors such as field area and sampling date (Donegan et al 1996;Wang et al 2013;Souza et al 2013). Little studies have been reported examining potential effects of transgenes on ecosystem in soil, the mineralization of crop residues, immobilization of nutrients and soil communities.…”
Section: Introductionmentioning
confidence: 99%
“…Little studies have been reported examining potential effects of transgenes on ecosystem in soil, the mineralization of crop residues, immobilization of nutrients and soil communities. Many field studies have displayed that the impacts on soil structure and microbial communities are transient and minor when compared to the factors caused by ecological and agronomic effects (Wang et al 2013;Wei Xiang et al 2006). Sources of soil enzymes including living and dead microbe, plant roots and soil animal residues play important functions in nutrient turnover and soil quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation